Cell and Molecular Mechanisms of Retinal Ganglion Cell Degeneration in Glaucoma - Yaghooti, Yalda; Shalbafan, Bita; Abdi, Fatemeh (Journal of Ophthalmic and Optometric Sciences, 2020)
Abstract Glaucoma is an eye disorder in which intraocular pressure is elevated and retinal ganglion cells therefore degenerate. It is a multifaceted ailment with multiple cell types and pathways involved, all working together and giving rise to optic nerve degeneration. Current drugs used in the treatment of glaucoma all work by lowering intraocular pressure and only slowing the progression of the optic nerve damage. No drugs have yet been shown to effectively target retinal ganglion cells and help regain the lost vision. It is of great importance to understand the cellular and molecular processes involved in glaucomatous neurodegeneration to be able to identify potential targets of treatment. The current review attempts to provide insight into these processes. First, an overview of the disease is provided and then, cell types other than retinal ganglion cells (RGCs) that contribute to the neurodegeneration process (including lamina cribrosa cells, astrocytes, oligodendrocytes, and microglia) and cellular and molecular events in the RGCs leading to their degeneration and death (such as mitochondrial dysfunction, axonal transport disruption, calcium dyshomeostasis, oxidative stress, apoptosis, and endothelial reticulum stress) are explained. Keywords: Glaucoma; Retinal Ganglion Cell; Neurodegeneration; Apoptosis; Cellular Components; Signaling Pathways.